The wild Thornberrys movie - Klasky, Arlene; Csupo, Gabor; Boutilier, Kate.; McGrath, Jeff.; Malkasian, Cathy; Chabert, Lacey, 1982-; Kane, Tom.; Summer, Cree.; Curry, Tim.; Redgrave, Lynn, 1943-; Flea (Musician); Tomei, Marisa; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2003)
Deep in the heart of Africa, the Thornberrys are filming their latest action-packed wildlife show. They are ready for anything, except for the greedy poachers lurking in the jungle. It's up to Eliza, who can talk to animals, to foil their evil plans. To do this, it will take all her courage, strength and exceptional gifts.
Special features: widescreen (16x9) and full screen presentation; music video: "Fathers and daughters" by Paul Simon; The wild Thornberrys PC game demo; theatrical trailer.
Editor, John Bryant ; music score, Drew Neumann ; production designer, Dima Malanitchev ; original character designers, Steve Fellner, Bill Schwab.
Lacey Chabert, Tom Kane, Cree Summer, Tim Curry, Lynn Redgrave, Flea, Marisa Tomei, Rupert Everett.
MPAA rating: PG; for some adventure peril.
DVD, Dolby digital, 5.1 Dolby surround, Region 1 encoding.
English or French dialogue; Closed-captioned.
Keywords: Safaris -- Africa -- Juvenile drama; Poachers -- Juvenile drama; Feature films; Animated films; Children's films; Films for the hearing impaired